MEMBANGUN KETAHANAN EKONOMI MELALUI SILATURAHIM - Yedi Purwanto (Jurnal Sosioteknologi, 2009)
In this article, the writer presents the result of analysis stating that there is a significant correlation between brotherhood and the economic resistance. The better the brotherhood among the components of nation, the higher the economic resistance will be, and vice versa. The responsibility of citizen is to improve the brotherhood among citizens, between citizen and government, and to maintain the harmony. Key words: brotherhood, resistance, economy